Indicators of rheumatoid arthritis disease activity. An association with a patient’s psychological status - V. V. Rybakova; Yu. A. Olyunin; E. V. Likhacheva; E. L. Nasonov (Современная ревматология, 2020)
Objective: to study of the relationship between psychological factors and indicators of rheumatoid arthritis (RA) disease activity in patients who have been followed up for a long time after initiation of treat-to-target therapy.Patients and methods. The investigation enrolled 38 RA patients (29 women and 9 men) aged 33 to 80 years (mean age, 56.5±12.5 years) with a mean disease duration of 6.0±0.9 years. All the patients underwent clinical examination; the following parameters were recorded: patient global assessment; physician’s global assessment; pain visual analogue scale (VAS), by measuring in millimeters; number of painful joints (NPJ), and number of swollen joints (NSJ). The investigators determined functional status with the Health Assessment Questionnaire (HAQ), quality of life with the 36-Item Short Form Health Survey questionnaire (SF-36), the nature of pain by the painDETECT questionnaire (PDQ), and the presence of anxiety and depression with the Hospital Anxiety and Depression Scale (HADS). The patients also filled out the Resilience (Res) Questionnaire (RQ) and the General Self-Efficacy ((GSE) Scale. Disease activity was evaluated by DAS28, CDAI, and RAPID3 scores. Results and discussion. RA disease activity was high in 4 patients, moderate in 21, and low in 9, and 4 patients had DAS28 remission. The average scores of RQ, its individual components, and GSE scale were comparable with the corresponding population scores for this age group. The patients who had RQ scores below the average group ones were noted to have significantly higher scores of patient global assessment; physician’s global assessment, NPJ, NSJ, CDAI, and RAPID3 than in those who had moderate and higher RQ scores. The similar trend was traced for individual Res components, such as involvement (INV), control (CONT), and risk acceptance (RA). However, the revealed differences in these indicators failed to reach statistical significance. There was no correlation between the measures of inflammatory activity and the result of GSE. The patients with subclinical and clinical anxiety and depression had significantly lower RQ, INV, and CONT scores than those who did not have anxiety or depression, whereas RA and GSE did not differ significantly in these groups. There was a significant positive correlation of Res, INV, and CONT with the quality of life, as assessed by SF-36. The findings suggest that low RQ scores can decrease the efficiency of the therapy performed (due to the patient’s poor compliance), on the one hand, and can corrupt the result of inflammatory activity assessment (due to the impact on a patient’s perception of his/her illness), on the other hand.Conclusion. The findings may suggest that there is a need to assess the psychological status of a patient when determining the level of RA disease activity.